Degradation of diferent types of polyethylene using for lining system exposed to hydro chloride acid solution - Dinh, Van Chau (ĐHCN, 2016)
This paper focuses on degradation behavior of a maleic anhydride modified and another new modified polyethylene used for lining system as anti-corrosion agent when exposed to hydrochloric acid solution environment. Different concentrations of HCl solution ： 0, 10, and 20 mass％at temperatures of 40, 60, and 80°C were set to investigate the degradation behavior of the two types of modified polyethylene. Virgin PE was also subjected to the same conditions for comparison. Weight change, chloride element penetration, and changes in chemical structure were measured. The immersion test result showed that the diffusion of water and the HCl solution into the neat PE obeyed Fickian diffusion model while those into both modified PE obeyed Fickian mode at low temperatures only. Two-saturation stages were observed for the samples immersed in HCl solutions at 80°C . The modified PE samples were degraded bythe HCl solutions while there was no change of chemical structure for the case of the PE resin. The high temperatureenhanced the order of degradation. IR spectra showed structural changes, which maybe attributed to the modifiercomponents in the polymers.